TINJAUAN KEBIJAKAN DALAM UPAYA PENGURANGAN RISIKO BENCANA DI KABUPATEN BLITAR, JAWA TIMUR - Kevie Desderius; Nasef Nanang Nugraha; Salieu Alimamy Sankoh; Setya Haksama; Ika Rahmawati; Catur Sudarmanto (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2025)
POLICY REVIEW IN DISASTER RISK REDUCTION EFFORTS IN BLITAR REGENCY, EAST JAVA Blitar Regency, located on the southern coast of Java Island, faces high disaster risk due to its geographical position bordering the Indian Ocean, the presence of the still-active Mount Kelud, and its hilly terrain. Revisiting disaster risk reduction policies in Blitar Regency is therefore essential. This study employs a qualitative approach using document analysis to examine disaster management policies at the international, national, and local levels. The analysis focuses on international policy frameworks such as the SFDRR and SDGs, as well as the implementation of national policies in accordance with the Disaster Management Law. The results indicate that policies in Blitar Regency have adopted principles from international and national frameworks, but require further strategic adjustments tailored to local conditions to enhance disaster risk reduction effectiveness. These findings form the basis for formulating policy strategies aligned with international, national, and local frameworks to address disaster threats in Blitar Regency.